Triathlon science - Friel, Joe; Vance, Jim 1976- (Human Kinetics, 2013)
Leave 'em in your wake, leave 'em in your trail, leave 'em in your dust. Get your brain as fit as your body and achieve your triathlon potential. Triathlon Science is packed with all the expertise you can handle, and more. From fine-tuning your physiology for each of the three disciplines to plotting the best race strategy for your fitness level, personal goals, and competitive conditions, you'll find the insights and prescriptions typically available only from a top-level coach. With editors Joe Friel and Jim Vance and a who's-who list of international experts on the sport, Triathlon Science offers you an unprecedented wealth of advanced yet accessible information on excelling in the sport.